Development of the logistical support mechanism for the airline’s innovation activity on the market of air transport services - Smerichevskyi , S.; Kryvovyazyuk, I.; Smerichevska, S.; Tsymbalistova, O. A.; Цимбалістова, О. А.; Kharchenko, M. V.; Харченко, М. В.; Yudenko, Ye. V.; Юденко, Є. В. (International Journal of Management. - 2020. - Vol. 11, Issue 6. - P. 1482-1492, 2020)
Визначено ключові аспекти матеріально-технічного забезпечення інноваційної діяльності авіакомпанії на ринку авіатранспортних послуг, розглянуто структуру інноваційної системи авіакомпанії, логістичний підхід до управління інноваційною діяльністю авіапідприємства. Уточнено цілі логістичної діяльності в контексті підтримки інноваційної діяльності авіакомпаній. Досліджено важливість та особливості матеріально-технічного забезпечення інноваційної діяльності авіакомпанії як системи управління інноваційним потоком. Розроблено та уточнено алгоритм формування механізму матеріально-технічного забезпечення інноваційної діяльності авіакомпанії. Створено дерево цілей підвищення ефективності матеріально-технічного забезпечення інноваційної діяльності авіакомпанії.

In this article the key aspects of logistical support of the airline’s innovation activity on the market of air transport services have been defined, the structure of the airline’s innovation system, logistics approach to managing the innovation activity of an airline enterprise have been considered and the main objectives of logistical activity in the context of innovation activity support of airlines have been clarified. The importance and peculiarities of logistical support of the airline’s innovation activity as an innovation flow control system have been studied. The algorithm of formation of the logistical support mechanism for the airline’s innovation activity has been elaborated and specified. The objectives tree for improving the efficiency of logistical support of the airline’s innovation activity has been created.

Определены ключевые аспекты логистического обеспечения инновационной деятельности авиакомпании на рынке авиатранспортных услуг, рассмотрены структура инновационной системы авиакомпании, логистический подход к управлению инновационной деятельностью авиапредприятия. Уточнены задачи логистической деятельности в контексте поддержки инновационной деятельности авиакомпаний. Исследованы важность и особенности логистического обеспечения инновационной деятельности авиакомпании как системы управления инновационными потоками. Разработан и уточнен алгоритм формирования механизма материально-технического обеспечения инновационной деятельности авиакомпании. Сформировано дерево целей повышения эффективности логистического обеспечения инновационной деятельности авиакомпании.
Keywords: інноваційна діяльність; innovation activity; инновационная деятельность; авіакомпанія; airline; авиакомпания; матеріально-технічне забезпечення; logistical support; материально-техническое обеспечение; інноваційні потоки; innovative flows; инновационные потоки